Evaluation the Efficiency of Subsurface Flow Constructed Wetland (SSF) for Wastewater Treatment and Reuse in Semi-arid Environment - Hadidi, Luna Al; Sweity, Amer (Journal of Agricultural Studies, 2022)
The efficiency of subsurface flow (SSF) constructed wetlands was evaluated on the treatment of secondary treated wastewater to improve the quality of the effluent for reuse purposes. A horizontal SSF system was constructed to evaluate the efficiency to enhance the quality of secondary treated wastewater effluent from Ramtha wastewater treatment plant WWTP and its potential uses for crop production at Hydrulic retention time HRT of 1 day. The SSF was planted with barley crop (Hordium vulgare), retrieved from the Arab Center for the Studies of Arid Zones and Dry-land (ACSAD) variety followed by corn crop (Zea mays L.), using BONANZA, F1 variety in the other season. Weekly physicochemical and microbiological analyses were carried out on the outlet from the wetlands in addition to the TWW treated wastewater effluent (inlet) in order to assess the removal efficiency of each stage of the treatment process and the total treatment system and it was used for irrigation of a fodder crop field. The SSF wetland subsequently influenced the physicochemical parameters. The SSF reduced the concentration of COD, NO-3, and TKN by 48%, 18%, and 20% respectively. Water use efficiency (WUE) for corn and barley were improved tremendously compared to the traditional irrigation techniques used in the field. The results showed a great possibility of using the SSF wetlands for the growth and production of fodder crops.